Mutational Analysis of Gene BRD2 in Patients of Juvenile Myoclonic Epilepsy - ., Hidayetullah (International Journal of Pathology, 2022)
Background: Epilepsy is characterized as third most common chronic brain disorder. It is known as by an enduring tendency to reduce seizures. Juvenile myoclonic epilepsy is the most frequent generalized epilepsy syndrome in adolescents or childhood. Juvenile myoclonic epilepsy based on finding of linkage analysis, is a genetic association study of photo paroxysmal response was carried out focusing on the BRD2 gene and its polymorphism in German population and other world population. Materials &Method: For this purpose, five epileptic families were identified, Blood samples were collected with two or more epileptic persons from different areas of Balochistan, and DNA was isolated by Inorganic method. Total 5 exons of BRD2 gene, harboring extensively reported mutations, were selected for genotypic analysis. PCR amplification and DNA sequencing of gene BRD2 (Bromodomain Containing Protein 2) was carried out to confirm any genetic variability in patients with familial inheritance in selected families. Results: During this study four different mutations were identified (c.610+35 insertion, c.145G>T, 146C>G, p.Ala49Cys, p.lys31lys, c.1062 T>C, p.Asn35Asn) in families with myoclonic epilepsy. Two of the variants are silent mutations; one is 1bp insertion in intron-4 while a missense substitution was also identified. The mutation is probably damaging which is confirmed by an online protein prediction tool Polyphen-2 prediction. Conclusions: It is concluded that highest percentage of Juvenile myoclonic epilepsies (JME) is in consanguineous marriage families. An important factor contributing to high incidence of Juvenile myoclonic epilepsies (JME) is the unawareness among people about the available diagnostic facilities for the prenatal diagnosis in Pakistan. Further studies involving larger number of patients aiming at genetic categorization of these patients may be helpful in better understanding of underlying pathophysiology.